OPTIMASI PRODUKSI DAN PENGUATAN MEREK POKLAHSAR NILA PELANGI AGAM UNTUK MENINGKATKAN NILAI TAMBAH OLAHAN PERIKANAN MANINJAU - Saniro, Roma Kyo Kae; Silmi, Silmi; Hidayat , Danny (Jurnal Abdi Insani, 2025)
Lake Maninjau is a freshwater fisheries center with significant production potential. However, the Agam Tilapia Pelangi Group (Poklahsar Tilapia Pelangi) as one of its drivers still faces limited production equipment, low hygienic practices, unattractive packaging, and suboptimal digital media utilization, resulting in suboptimal product value and market expansion. This community service program aims to increase the added value of fishery products through production optimization and strengthening group branding. The program was implemented using a Participatory Action Research (PAR) approach through problem identification, outreach, hygienic production training, modern equipment procurement, packaging design training, product photography, and digital marketing assistance, which were evaluated through observation and active participation of partners. This program increased production capacity by 30% in six months, extended product shelf life through s packaging, and improved quality standards through the use of modern equipment. In terms of marketing, packaging design and digital marketing training strengthened the product's visual identity, including the use of paper bags with the group's logo as a collective identity, and activated promotions through Instagram and WhatsApp Business, which are projected to increase online sales by 10%. These results indicate that the integration of production optimization, packaging innovation, and digital marketing effectively increases the competitiveness of the Tilapia Pelangi Group. Sustainability is directed at routine mentoring, halal certification and distribution permits, product diversification, and integration of a digital village roadmap to strengthen business independence.